Impementasi Project Based Learning Dalam Pembelajaran Abad 21 Pada Mata Pelajaran Geografi Kelas XI IPS SMA Nasional 3 Bahasa Putera Harapan Purwokerto - Ika Pujiastuti (UM Purwokerto Press, 2021)
The development of curriculum in schools is currently required to make changes in implementing teacher-centered learning approaches into student-centered learning approaches. This is adjusted to the demands of learning that will affect the development of children in the future, where children must have thinking and learning skills. These skills include critical thinking skills, problem solving, collaboration, and communication skills. These skills are often said to be skills in the independent learning process that must be possessed by students. Students can have these skills if the teacher is able to develop learning with activities that challenge students to think critically in solving problems. Another aspect that is no less important is the Assessment or Assessment. Assessment can be given among students as feedback, by the teacher with an assessment rubric that has been prepared by the teacher or based on the performance and products they produce. To achieve the aforementioned objectives, a learning approach that is quite challenging for teachers is a project-based learning (PBL) approach.